Rejection of malathion by nanofiltration and reverse osmosis membranes exposed to foulant and two clean-in-place procedures - Mikelonis, Anne M.; Orme, Christopher J.; Nilkar, Amit S.; Szabo, Jeffrey G.; Reese, Stephen J. (Water science & technology. Water supply, 2024)
This research tested the treatment efficacy of an Energy Savings Nanofiltration 1 Low Fouling (ESNA 1-LF) nanofiltration (NF) and an Energy Saving Polyamide 2 (ESPA2) reverse osmosis (RO) membrane for removing malathion from water. Both membranes are of composite polyamide construction. The study included measuring malathion rejection using both pristine membranes and membranes exposed to a simulated secondary wastewater effluent foulant before and after two types of clean-in-place procedures. Across all conditions studied, malathion rejection ranged from 84 to 95% for the ESNA1-LF NF membrane and 77 to 94% for the ESPA2 RO membrane. Contact angle measurements were also collected for each membrane exposure condition. While the contact angle measurements indicated changes to the hydrophobicity of the selective layer of the membranes, they did not correlate to changes in the performance of malathion rejection. As expected, it was observed that malathion rejection improved with the introduction of foulant. Also, the clean-in-place procedures helped restore flux while maintaining malathion rejection.